How Challenge Demands Have Offsetting Effects on Job Performance: Through the Positive and Negative Emotions - Wang, Qiong; Xia, Aijing; Zhang, Wei; Cai, Zijun; Zhang, Xiyang; Teng, Xiaofei; Zhang, Jing; Qian, Jing (Frontiers in Psychology, 2021)
By combining the broaden-and-build theory of positive emotions (Fredrickson, 2001) and the transactional theory of stress (Lazarus & Folkman, 1984), this study examines how challenge demands (i.e., task complexity, time pressure) have dual effects on employees’ job performance through the mediating effects of positive and negative emotions. We collected data from 414 employees from three firms located in China, including two hi-tech firms and one financial firm. The results indicated that challenge demands (i.e., task complexity, time pressure) have an overall positive effect on employees’ job performance (i.e., task performance, contextual performance) by offsetting positive indirect effects with negative indirect effects. The theoretical and practical implications are also discussed.